Thyroid Hormone and Neural Stem Cells: Repair Potential Following Brain and Spinal Cord Injury - Vancamp, Pieter; Butruille, Lucile; Demeneix, Barbara A.; Remaud, Sylvie (Frontiers in Neuroscience, 2020)
Neurodegenerative diseases are characterized by chronic neuronal and/or glial cell loss, while traumatic injury is often accompanied by the acute loss of both. Multipotent neural stem cells (NSCs) in the adult mammalian brain spontaneously proliferate, forming neuronal and glial progenitors that migrate towards lesion sites upon injury. However, they fail to replace neurons and glial cells due to molecular inhibition and the lack of pro-regenerative cues. A major challenge in regenerative biology therefore is to unveil signaling pathways that could override molecular brakes and boost endogenous repair. In physiological conditions, thyroid hormone (TH) acts on NSC commitment in the subventricular zone, and the subgranular zone, the two largest NSC niches in mammals, including humans. Here, we discuss whether TH could have beneficial actions in various pathological contexts too, by evaluating recent data obtained in mammalian models of multiple sclerosis (MS; loss of oligodendroglial cells), Alzheimer’s disease (loss of neuronal cells), stroke and spinal cord injury (neuroglial cell loss). So far, TH has shown promising effects as a stimulator of remyelination in MS models, while its role in NSC-mediated repair in other diseases remains elusive. Disentangling the spatiotemporal aspects of the injury-driven repair response as well as the molecular and cellular mechanisms by which TH acts, could unveil new ways to further exploit its pro-regenerative potential, while TH (ant)agonists with cell type-specific action could provide safer and more target-directed approaches that translate easier to clinical settings.